AB0789 The Clinical Effects of Post-Operative Anterior-Posterior Length Mismatch in Distal Femur with after Total Knee Arthroplasty. (10th June 2014) - Nishikawa, M.; Owaki, H.; Fuji, T.
Abstract : Background: Recently, anatomic differences of the distal femur in gender and races were reported. Especially in total knee arthroplasty (TKA), relationship between the anterior-posterior (AP) length and the medial-lateral width of the distal femur is very important in implant design. Because majority of implants current used in Japan were designed using Caucasian distal femoral anatomy, anatomical size mismatch in Japanese distal femur were seen in some cases. Objectives: The objectives of this study were to evaluate the clinical effects of post-operative anterior-posterior length mismatch in Japanese distal femur after TKA, by measuring the differences between pre-operative and post-operative AP length in distal femur. Methods: Two-hundred two Japanese patients who underwent TKA in Osaka Koseinenkin Hospital from April, 2009 to August, 2012 were included in this study. The genders and diagnoses were 28/174 patients (male/female) and 162/40 patients [osteoarthritis/rheumatoid arthritis], respectively. The mean age, height and body weight were 73.0 years, 152.1 cm and 53.7 kg, respectively. We defined the AP length as the length between top of lateral flange and bottom of lateral posterior condyle. We measured the pre-operative AP length using computed tomography. We defined the post-operative AP length as femoral component AP length provided from manufactures. We measured the differences from post-operative to the pre-operative AP length. We classified them into 3 groups (Smaller: difference <-2mm, Same: -2≤ difference ≤2mm, Bigger: difference >2mm). We evaluated the post-operative range of motion (ROM) and Knee Society scores (Knee score: KS and Function score: FS) in these 3 groups at 1 year follow-up. Results: The numbers of 3 groups (Smaller/Same/Bigger) were 54/112/36, respectively. The pre-operative knee extension angles in 3 groups (Smaller/Same/Bigger) were -10.9 degrees/-12.2 degrees/-12.1 degrees, respectively. The pre-operative knee flexion angles were 127.3 degrees/119.2 degrees/125.6 degrees, respectively. The pre-operative KS were 33.0/32.1/31.2, respectively. The pre-operative FS were 51.9/48.7/49.6, respectively. The pre-operative ROM and Knee Society scores in 3 groups were not significant. The post-operative knee extension angles in 3 groups (Smaller/Same/Bigger) were -2.1 degrees/-2.6 degrees/-4.9 degrees, respectively. The post-operative knee flexion angles were 128.1 degrees/124.0 degrees/123.9 degrees, respectively. The post-operative KS were 95.4/95.7/93.5, respectively. The post-operative FS were 77.3/73.2/72.6, respectively. The post-operative ROM and Knee Society scores in 3 groups were not also significant. Conclusions: Although we hypothesized that anatomical AP length mismatch after TKA affect the ROM and Knee Society scores because of unbalanced extension-flexion gap, there were no significant difference in 3 groups. In conclusion, the post-operative anterior-posterior length mismatch in distal femur after TKA did not affect clinical results at 1 year follow-up, however we have to pay attention to the effect of component loosening and clinical results in long-term follow-up. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1287